PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) BERBANTUAN MEDIA VIDEO ANIMASI TERHADAP HASIL BELAJAR SISWA KELAS V SDN 37 PEKANBARU - Tasya Delfika; Adi Putra, M. Jaya; Alpusari, Mahmud (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is backround by the low learning outcomes of students in the subject of Science, which is caused by the lack of student activity in the learning process and difficulty in understanding abstract material, especially in the material of Electrical energy. This study aims to determine the effect of the Project Based Learning (PjBL) learning model assisted by animated video media on the learning outcomes of fifth grade students of SDN 37 Pekanbaru. The research method used is a quantitative approach with a One Group Pretest-Posttest Design. The research sample consisted of 27 students. The instrument used was a learning outcome test that had been tested for validity and reliability. Data analysis was carried out through showing that the average student pretest score of 35.48 increased to 68.07 in the posttest with an increase of 32.59. The results of the paired sample t-test showed a significance value of 0.000 <0.05, which means there is a significant effect of the application of the PjBL model assisted by animated video media on student learning outcomes. Furthermore, the N-Gain test result of 0.5241 is in the moderate category, indicating that this learning model is quite effective in improving learning outcomes. Thus, it can be concluded that the implementation of the Project Based Learning model assisted by animated video media has a positive and significant impact on student learning outcomes